Intermittent cooling during Judo training in a warm/humid environment reduces autonomic and hormonal impact - Carballeira, E.; Morales, J.; Fukuda, D. H.; Granada, M. L.; Carratalá-Deval, V.; López Diaz de Durana, A.; Stout, J. R. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to identify the effects of superficial cooling on physiological responses while training in a warm, humid environment during an international Judo training camp. Sixteen judokas (8 women and 8 men) participated in the experiment. Four high-level women and 4 men were randomly assigned to wear a cooling vest (vest group [VG]) during the recovery periods within a training session (i.e., 8 bouts of 5-minute fighting with 5-minute rest) and up to 10 minutes after the session, whereas the remaining athletes in the control group (CG) trained without the use of any cooling aids. No differences between groups were reported in well-being before the session or in perceived fatigue after the session. The temperature was increased after the training session (p = 0.02) without significant differences between groups; however, CG demonstrated a moderate effect size (ES = 0.95, 90% confidence interval [CI] = 0.09-1.82; probability of superiority [PS] = 74.9%) in contrast to the small effect for VG (ES = 0.28, 90% CI = -0.55 to 1.11; PS = 57.9%). There were time × group interactions for heart rate variability (lnRMSSD) (p = 0.006; VG vs. CG, PS = 79.0%) and the dehydroepiandrosterone-cortisol ratio (DHEA/C ratio) (p = 0.04; VG vs. CG, PS = 99.9%). Vest group preserved the cardiac autonomic control (p > = 0.05; ES = -0.06, 90% CI = -0.88 to 0.76; PS = 51.7%) compared with the large decrement of CG (p < 0.05; ES = -1.18, 90% CI = -2.07 to -0.29; PS = 74.9%). Furthermore, VG showed an increase of DHEA/C (p = 0.002) from presession to postsession based on a moderate decrease of cortisol (p > = 0.05; ES = -0.67, 90% CI = -1.52 to 0.17; PS = 68.2%) with a concomitant small increase of DHEA (p > = 0.05; ES = 0.46, 90% CI = -0.38 to 1.29; PS = 62.7%). Conversely, the CG showed a moderate effect for increased DHEA and a small effect for increased cortisol after training. No significant interactions or main effects were shown for isometric handgrip values. Cooling vests diminished the cardiovascular strain and hormonal impact of the Judo training session in high-level athletes and may be considered for recovery purposes during exercise in warm/humid environments.